Case Report: Multiple Liver Nodules Due to Type 2 Diabetes Mellitus in a 55-Year-Old Male Patient - Billy Oktavian; Cristina Tarigan (Green Publisher Indonesia, 2024)
Hepatic cirrhosis is characterized by fibrosis and formation of liver nodules caused by chronic injury, causing changes in the normal lobular organization of the heart. Hepatic cirrhosis can occur in all genders and about two-thirds occurs in men and one part in women. Diabetic patients can experience insulin resistance, which can be the basis for the development of complications into liver cirrhosis. This case study describes a 55 year old male patient who was diagnosed with hepatic cirrhosis with diabetes mellitus and discussed the course of the disease to the therapy given to the patient. A 55 year old male patient came with complaints of shortness of breath that had been felt for 3 months before entering the hospital. Based on the history, physical examination and search, the patient was diagnosed with liver cirrhosis, multiple liver nodules, type 2 diabetes mellitus and pulmonary tuberculosis. Hepatic cirrhosis can be caused by various diseases, one of which is diabetes mellitus. Diabetes can progress to nonalcoholic fatty liver disease and eventually to cirrhosis and hepatocellular carcinoma. Insulin resistance syndrome is the main factor that can cause cirrhosis in diabetes patients. Early diagnosis, resistance and control of risk factors as well as appropriate treatment also play an important role in reducing the damage to the prognosis of patients with hepatic cirrhosis due to diabetes mellitus.